Pengaruh Harga dan Electronic Word Of Mouth (E-WOM) terhadap Keputusan Pembelian di Ragam Garden’s di Kabupaten Bogor - Ryanda, Chiko; Solihin, Dede (Multidisciplinary Journal of Education , Economic and Culture, 2025)
This study aims to determine the effect of price and electronic word of mouth on purchasing decisions at Ragam Garden's, Bogor Regency. The quantitative research method uses regression analysis techniques. The results of this study indicate that price has a positive and significant effect on purchasing decisions, Electronic word of mouth has a positive and significant effect on purchasing decisions. Simultaneously, there is a positive and significant effect of price and electronic word of mouth on purchasing decisions.